2013
DOI: 10.4103/0974-2700.115332
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy as prognostic marker in acute traumatic brain injury

Abstract: Context:Coagulopathy frequently occurs following traumatic brain injury (TBI) and usually occurs 6-72 hour post-trauma. The incidence and the probable risk factors for development of coagulopathy and poor outcome following TBI are largely unknown and vary considerably.Aims:To assess the incidence and probable risk factors for development of coagulopathy and to identify the risk factors for poor outcome in terms of median survival time following TBI.Materials and Methods:In this prospective study over two years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…utilized similar criteria and observed the incidence to be 46%. [ 30 ] In our study, development of coagulopathy was associated with longer ICU stay; it correlates with the literature. [ 31 ] The presence of TBI coagulopathy in our study was associated with 3.13-fold increased risk of mortality which is contrary to the results by Affonseca et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…utilized similar criteria and observed the incidence to be 46%. [ 30 ] In our study, development of coagulopathy was associated with longer ICU stay; it correlates with the literature. [ 31 ] The presence of TBI coagulopathy in our study was associated with 3.13-fold increased risk of mortality which is contrary to the results by Affonseca et al .…”
Section: Discussionsupporting
confidence: 90%
“…Reported incidence of coagulopathy in TBI patients ranges from 10% to 97%. [ 24 25 26 27 28 29 30 ] Our study suggests 33%. The wide variation is due to different criteria used by different authors.…”
Section: Discussionmentioning
confidence: 68%
“…reported GCS <8, effaced cistern, Hb <10 g/dl, and D-dimer >1 mg/dl strongly predict the development of coagulopathy. [ 19 ] Similarly, we also found Hb <10 g/dl is a significant predictor of coagulopathy among the adult TBI group but not in the pediatric TBI group. In our study, we also observed that leukocytosis (total lung capacity >11,000) is strongly correlated with coagulopathy among the adult population, but same does not hold true for the pediatric group.…”
Section: Discussionsupporting
confidence: 65%
“…Other researches have already focused on the relation between partial thromboplastin time test and TBI prognosis. In 2013, Chhabra et al reinforced the high incidence of coagulopathy following TBI and demonstrated that the presence of coagulopathy is a strong predictor of in-hospital mortality (29). In agreement with these results, a recent article by Yuan et al revealed that coagulation tests could improve the predictive power of the standard models for in-hospital mortality after TBI (30).…”
Section: Discussionmentioning
confidence: 90%